Monopsonistic Labour Markets and the Gender Pay Gap: Theory and Empirical Evidence - Hirsch, Boris (Springer, 2010)
This book investigates models of spatial and dynamic monopsony and their application to the persistent empirical regularity of the gender pay gap. Theoretically, the main conclusion is that employers possess more monopsony power over their female employees if women are less driven by pecuniary considerations in their choice of employers than men. Employers may exploit this to increase their profits at the detriment of women's wages. Empirically, it is indeed found that women's labour supply to the firm is less wage-elastic than men's and that at least a third of the gender pay gap in the data investigated may result from employers engaging in monopsonistic discrimination. Therefore, a monopsonistic approach to gender discrimination in the labour market clearly contributes to the economic understanding of the gender pay gap. It not only provides an intuitively appealing explanation of the gap from standard economic reasoning, but it is also corroborated by empirical observatio
WiSo-Import:2015-04-13:481
Keywords: Transformation; Forschungsbericht 2010